PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN KARYAWAN (STUDI KASUS PADA BANK BRI CABANG TAMBUSAI PEKANBARU) - Maizir, Rafki Priandani; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research was conducted at the Institute of Ganesha Smart TutoringBranch Panam Pekanbaru in order to determine the organizational culture ofemployees (Case Study at Bank BRI Branch Tambusai Pekanbaru. Variable inthis research are: organizational culture and commitment to employees. Thesample in this study were 55 people with using census techniques. The method ofanalysis is simple regression analysis. Based on the results of the study showedthat there is influence of organizational culture on employees' commitment tousing the coefficient of determination is KD = r 2 x 100% = (0532) 2 x 100% =0.283 means that the value of average commitment amounted to 28.3% ofemployees are determined by the culture of the organization. Furthermore, theresults obtained regression equation Y = 16 256 + 0.225 X. The equation showsthat if the organizational culture is increased by 1 unit will affect the increase inemployee commitment for 0225, it is seen from b is a positive value. Results ofhypothesis testing t = 6937> t table = 2.000 at 95% confidence level. based onthese results that there is the influence of organizational culture on employeecommitment (Case Study at Bank BRI Branch Tambusai Pekanbaru).Keywords: Cultural Organization, Employees Commitment